Effectiveness of Combined Verbal Screening and Uniform Donor Questionnaire in Blood Donor Deferral; Evaluation at a Regional Blood Bank - Maria Khan, Saima Bashir, Muhammad Abdul Naeem, Mansoor Ishaq Raja, Muhammad Ali Rathore, Sadia Babar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Blood transfusion is a potentially life-saving procedure that replaces the blood lost either during surgery or after injury. It also serves as a mean of replacing blood in the patients who cannot replenish enough blood for their own body. Donors come from all walks of life with established lifestyle. A detailed questionnaire along with verbal screening and general physical examination should be performed in all blood donors before labeling them unsuitable for donation. Objective: To evaluate the effectiveness of verbal screening in addition to uniform donor questionnaire as a routine pre-donation protocol for donor selection and deferral. Material and Methods: This cross-sectional study was conducted at a regional blood bank in Northern Pakistan over a period of six months from January 2021 to June 2021. The blood donors who were deferred after assessment by uniform donor questionnaire (UDQ), verbal screening and general physical examination were critically analyzed. The causes of deferral were noted. The data was analyzed by using SPSS Version 23. Results: A total of 400 blood donors were deferred during the study period. Their ages ranged from 25 to 40 years with a median age of 29 years. Majority of them were males (97.5%). Among these, 332 were deferred on uniform donor questionnaire, 48 on verbal screening and 20 on general physical examination. Conclusion: Assessment of blood donors by verbal interview as an adjunct to donor questionnaire is very effective in donor selection and deferral process and should be made a mandatory part of pre-donation blood donor selection protocol. Keywords: Transfusion, uniform donor questionnaire, verbal screening